Sistem Informasi dan Pendaftaran Pasien pada PUSKESMAS Kelapa Dua Kabupaten Tangerang, Banten - Fenina Adline Twince Tobing; Adhi Kusnadi; Eunike Endariahna Surbakti; Niki Prastomo; Johan Setiawan; Rangga Winantyo (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Health Center (Puskesmas) is a technical implementation unit of the District/City Health Office responsible for implementing health development in a specific working area. Puskesmas Kelapa Dua is the first health center in Kelapa Dua Subdistrict, Tangerang Regency. The registration process at Puskesmas Kelapa Dua has been done manually, where patients or participants have to come and wait for a long time just to register and get a queue number for treatment. Therefore, the Patient Information and Registration System was developed for Puskesmas Kelapa Dua, Tangerang Regency, Banten. This activity aligns with the planned objectives and benefits, which are to assist Puskesmas Kelapa Dua in providing information to the community and facilitating patient registration for treatment in an easier, more practical, time-saving, real-time manner, without wasting much time, cost, and effort. This is achieved through a mobile phone-accessible application. The results were obtained from testing, including functional testing where all system functions worked well, environment testing conducted on various browsers with no issues, and User Acceptance Testing (UAT) where user satisfaction was evaluated, and the system successfully met user expectations